Vitamin D and Diabetic Retinopathy in Indian adults with Type 2 Diabetes Mellitus - Dinesh R B.; Anil Kumar. R (International Journal of Medical Research and Review, 2018)
Objective: To find an association with Vitamin D levels and Diabetic retinopathy (DR).Methods: In a prospective clinical study, 412 Type 2 DM patients were evaluated for their ophthalmic findings. All patients underwent complete ophthalmic examination including detailed history, best corrected visual acuity, slit lamp examination, indirect ophthalmoloscopy and +90D lens biomicroscopy. All relevant blood investigation for evaluation of glycemic status including Vitamin D was done on first presentation.Results: Among the 412 patients that were examined, thepercentage of patients with HbA1C <6.4 was 15%, 6.5- 8.0 was 31% and >8.0 was 54%. Among 222 patients with >5 years duration of DM, 95(43%) had HbA1C >8.0. Among 96 patients with 5-10 years duration of DM, 67 (70%) had HbA1C .8.0. Among 94 patients with>10 years duration of DM, 59(63%) had HbA1C >8.0, with a significant P value of <0.001. Among 412 patients, 7% had vitamin D levels >30, 13% had levels between 20-30 and 80% had <20. A significant P value of <0.001 was seen with respect to association of DR with HbA1C levels.Conclusions: Type 2 DM patients with retinopathy were found to have significant vitamin D deficiency as compared to those without retinopathy.